Analisis Stakeholder Pengelolaan Sumber Daya Hutan di Kabupaten Jember - Candra Hidayat, Nurhuda; Setijaningrum, Erna; Asmorowati, Sulikah (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This study aims to analyze stakeholders in forest resource management in Tugusari Village, Bangsalsari District, Jember Regency. This research is motivated by the drastic reduction of critical land in Jember Regency, or in other words, there is success in forest conservation. In answering the problem formulation using Overseas Development Administration theory to identify stakeholders. Meanwhile, for the categorization and interrelation of stakeholders using Reed's theory. This study uses descriptive qualitative method. The results of this study have identified primary, secondary and key stakeholders. The primary stakeholders were LMDH Wana Makmur and the Tugusari Village Government. Secondary stakeholders are PWH Unit VII Bondowoso Jember working area. The key stakeholder is the public company Perhutani KPH Jember. Meanwhile, the stakeholder category consists of key players, contact setters, subjects and crowd. The key category is the public company Perhutani KPH Jember. The contract setters, namely the Village Government. Subjects were LMDH Wana Makmur and Crowd, namely UPT PWH VII Bondowoso, Jember working area. While, the interrelation between LMDH Wana Makmur stakeholders and the public company Perhutani KPH Jember went good because they often held coordination meetings and collaborative involvement